Modelo de programação linear inteira para o Problema de Alocação de Salas: estudo de caso em uma Instituição de ensino superior - Silva, Luciano Fernandes Acioli Cabral e (2019)
Allocating classes to classrooms is a problem experienced every semester in all educational institutions. This problem is known as the Classroom Assignment Problem and consists of the efficient allocation of classes, with pre-established days and times, to classrooms, taking into account the needs of teachers, students, classes and respecting the capacity of the classrooms. Generally, this problem is solved by the institutions manually, however, because it is a combinatorial problem, manually, this process can take several days and still not get satisfactory results. Due to its importance, difficulty of solving and its own characteristics that make difficult a generalized solution, this problem has been widely studied. In this research, the Informatics Center of the Federal University of Para´ıba was taken as a case study for the Classroom Assignment Problem. An integer linear programming model was developed and a computerized system that makes use of this model to solve this problem and can be used in practice by those responsible for room allocation at the UFPB Informatics Center.